Biopesticides to Control Anthracnose Disease in Chili Pepper (Capsicum annuum L.): A Review - Ni Kadek Desy Andya Dewi; Ni Luh Putu Sulis Dewi Damayanti; Anak Agung Sagung Putri Risa Andriani (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
Anthracnose disease is one of the most destructive diseases affecting chili pepper (Capsicum annuum L.). The impact of anthranose on production worldwide results in significant yield and quality losses during both pre-harvest and post-harvest stages. Control of this disease has relied use traditional technic with synthetic fungicides. Synthetic fungicides have caused pathogen resistance, environmental contamination, and food safety concerns. Therefore, biopesticides are considered an environmentally friendly and sustainable alternative. This review aims to critically summarize recent studies published between 2015 and 2025 on the application of biopesticides to controlling anthracnose disease in chili pepper. Scientific literature was collected from major databases, including Scopus, ScienceDirect, and Google Scholar. The review highlights the effectiveness of biopesticides from microbial and botanical pesticides. Microbial pesticides such as Trichoderma spp., Bacillus, and Pseudomonas spp. Contribute to disease suppression by producing antimicrobial metabolites and inducing systemic resistance in host plants. Botanical pesticides based on plant extracts and essential oils have antifungal activity by inhibiting spore germination, disrupting fungal cell structures, and antimicrobial chemical compounds. Although biopesticides potential to control anthracnose disease, but remains inconsistent due to environmental factors and formulation constraints. Therefore, improved formulation technologies and integration into integrated disease management strategies are essential to enhance their reliability and adoption in sustainable chili production systems.